1999
DOI: 10.1089/088922299309937
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea and Enteric Emerging Viruses in HIV-Infected Patients

Abstract: To evaluate the prevalence of enteric viruses and their possible association with diarrhea, 244 stool samples were collected from HIV-infected and uninfected patients with or without diarrhea (subgroups I-a, Ib, II-a, and II-b, respectively). Subjects were screened by polyacrylamide gel electrophoresis, latex agglutination, and enzyme immunoassays for rotaviruses, adenoviruses, picobirnaviruses, and astroviruses. Enteric viruses were found significantly more often in specimens from HIV patients (20%) than in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…HAstVs affect predominantly the pediatric population (117,164,229,230), although infections in elderly people and immunocompromised hosts are also reported (231)(232)(233)(234)(235)(236). In addition, astrovirus gastroenteritis may also affect healthy adults (88,89,207).…”
Section: Age Geographic and Temporal Distributionmentioning
confidence: 99%
“…HAstVs affect predominantly the pediatric population (117,164,229,230), although infections in elderly people and immunocompromised hosts are also reported (231)(232)(233)(234)(235)(236). In addition, astrovirus gastroenteritis may also affect healthy adults (88,89,207).…”
Section: Age Geographic and Temporal Distributionmentioning
confidence: 99%
“…The primary objective of these environmental studies was to evaluate PBV as an indicator of fecal contamination, the potential health risk of the presence of PBVs in sewages and natural water resources should not be neglected and this finding deserves further investigations. Studies in immuncompromised and immunosuppressed hosts indicated that these viruses might be 'opportunistic pathogens' [38,39,41,42,44,75,80].…”
Section: Discovery Of Picobirnavirusmentioning
confidence: 99%
“…Thus, the probable role of PBV as either a primary diarrhoeal agent in immunocompetent children [6,7], a potential pathogen in immunocompromised individuals [38,39,44] or an innocuous virus in the intestine remains elusive and needs to be investigated despite the numerous reports of the presence of PBV in fecal samples of various hosts species; our current knowledge of their biology, etiology, pathogenicity or their transmission characteristics remains subtle [15,32,33,57], mainly because of their non-cultivable status (in vivo and in vitro) that is, the absence of a cell culture system and suitable animal model for propagating the virus. Further studies in gnotobiotic animals may shed light on PBV pathogenic potential [15].…”
Section: Discovery Of Picobirnavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the numerous reports of the presence of PBV in fecal samples from vertebrates, the pathogenicity of these viruses has not been established. However, studies conducted with human immunodeficiency virus-infected persons (13,15) suggest that PBV may be an opportunistic pathogen that may cause diarrhea in immunosuppressed individuals.…”
mentioning
confidence: 99%